Causal Model of the Influence of Instructional Leadership, Teacher Competence, and Work Culture on Educational Quality in Public Junior High Schools - Wiwik Widayati; Maryanto; Ngasbun Egar (Jurnal Ilmiah Pendidikan dan Pembelajaran, 2025)
Improving the quality of education is a strategic challenge that requires synergy between instructional leadership, teacher professionalism, and school work culture. This study aims to analyze the causal model of the influence of instructional leadership, teacher professional competence, and work culture on educational quality. A quantitative approach with a correlational design was used, involving 173 teachers as respondents selected through a proportional random sampling technique. Data were collected using a standardized questionnaire that had been validated and tested for reliability. Data analysis was conducted using descriptive statistics to describe the characteristics of the respondents, correlation analysis to assess the strength of the relationship between variables, and multiple regression to estimate the contribution of independent variables to the variance in educational quality. The results showed that instructional leadership, teacher professional competence, and work culture each had a positive and significant effect on academic quality. The correlation coefficient indicated a strong relationship between the three variables and educational quality, while multiple regression analysis revealed a simultaneous contribution of 57.8% (R² = 0.578) to the variation in academic quality. This study also assessed the instrument's consistency through Cronbach's alpha calculation and conducted tests for the classical assumptions of normality, multicollinearity, and heteroscedasticity to ensure the reliability of the regression estimates. Theoretically, this study enriches the literature on the causal interactions of the three dimensions; practically, the findings are recommended for stakeholders to design key capacity-building interventions.